Self-concept Perempuan Pekerja Pemulung (Studi Kasus Perempuan Pekerja Pemulung Kota Harapan Indah) - Reniati, Isni; Setiawan, Rizki; Hayat, Nurul (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Women waste pickers in Kota Harapan Indah, despite facing social stigma and social discrimination, can still show resilience in overcoming challenges and problems in their work. The self-concept of women waste pickers is formed through social and personal perceptions, social relationships, and self-experiences that ultimately form the basis for understanding how they adapt to challenging environments. This study aims to find out and describe the self-concept of women scavenger workers. This research uses a qualitative approach with a case study method. The study data were collected through participatory observation, semi-structured interviews, and documentation. The results showed that women waste pickers in Kota Harapan, Indonesia, experienced a negative social perception from the community regarding their work. This social stigma influences the formation of self-concept in the imagination through shadows of self-appearance, judgment, and emotional feelings. In addition, social interaction, both with family, fellow waste pickers, and the surrounding community, has an important role in shaping the self-concept of women scavenger workers. Positive feedback from the social environment can increase the self-confidence and self-acceptance of women scavengers. This research shows that the self-concept of women scavengers is influenced by people's perceptions, social relationships, and personal experiences. This self-image is the result of complex interactions between individuals and their environment. The conclusions in this study show how social and self-perceptions, social relationships, and self-experiences have a significant role in shaping the self-concept of women scavenger workers.